Energy losses in crystalline silicon rooftop photovoltaic systems in selected site locations in Sub-Saharan Africa - Ebhota, Williams S.; Tabakov, Pavel Y. (Center of Biomass & Renewable Energy (CBIORE), 2024)
This study systematically evaluates Phototovoltaic (PV) system energy losses and performance quality across selected locations in sub-Saharan African (SSA). Utilising a computational model for a hypothetical 10 kWp crystalline silicon (c-Si) PV system, the research categorises energy losses into irradiance (kWh/m²) and electricity production (kWh/kWp). Key contributors to irradiance losses include angular reflectivity, dirt, dust, and soiling, while inverter and radiation conversion, spectral correction, transformer and cabling, and mismatch are identified as main sources of PV system energy losses. Tilt and orientation impact the transformation of Global Horizontal Irradiance (GHI) into Global Tilted Irradiance (GTI), with the highest gain in Pretoria (215.4 kWh/m²) and the least in Kinshasa (3.6 kWh/m²). The study notes the highest PV system energy loss in Pretoria (346.2 kWh/kWp) and the least in Kinshasa (267.4 kWh/kWp). Despite variations in energy loss sources, the cumulative degradation rate is reported as 12.8% for all locations over a 25-year lifespan. The annual average performance ratio (PR) and capacity factor (CF) range from 77.4%/19.7% in Pretoria to 77.4%/15.6% in Kinshasa. Ambient conditions, including wind speed, relative humidity, precipitation, and temperature, are identified as key factors influencing solar irradiance and PV system losses. The study suggests preventive measures such as optimal system design, the use of bypass diodes, and high-quality PV panels.